Relationship between social media addiction and impulsivity in schoolchildren of public educational institutions in East Lima - Campos Bartolo, Laura (2020)
Objective: To determine the relationship between addiction to social networks and impulsiveness in the students of 4th and 5th grade of secondary school of two state educational institutions of East Lima. Methodology: Non-experimental design, quantitative approach, cross-sectional and correlational type. The measurement of the impulsivity variable was the Barratt Impulsivity Scale in early adolescents (BIS- 11-A) which contains two dimensions: general impulsivity and unplanned impulsivity. Regarding the social network addiction variable, the Social Network Addiction Risk Scale (CrARS) was used, which contains seven dimensions, prepared by Vilca and Vallejos (2015). Results: The sample consisted of 253 students, of both sexes, whose ages were 15-17 years. A significant relationship was found between impulsivity and social media addiction (rho = .445, p <.01). Conclusion: That students who have high levels of impulsivity are related to a higher risk of addiction to social networks